Coadjuvant hypoglycemiant effect of Annona muricata L (guanabana) leaves ethanolic extract in patients with type 2 diabetes mellitus receiving glibenclamide treatment - Arroyo, Jorge (2009)
Objective: To determine efficacy and security of of Annona muricata L (guanábana) leaves ethanolic extract plus glibenclamide capsules in controlling glucose levels in type 2 diabetes mellitus patients compared to patients receiving with glibenclamide alone. Design: Randomized, double-blind, parallel-group controlled clinical trial. Setting: Internal Medicine service, Tingo María-EsSalud Hospital I, Huanuco city. Par ticipants: Type 2 diabetes mellitus patients. Interventions: Between May 2007 and September 2007 sixty 38 to 60 year-old patients were randomly assigned to 6 groups, 3 receiving capsules containing 180 mg of Annona muricata L leaves ethanolic extract plus glibenclamide 5 mg and 3 receiving glibenclamide 5 mg tablets only. Main outcome measurements: Reduction of glycemia. Results: There was reduction of glycemic levels, higher in those receiving guanabana plus glibenclamida. Auxiliary exams did not reveal adverse effects. Two cases presente epigastric pain, one of them associated with nausea, and three cases presented only nausea. Conclusions: Treatment with capsules containing Annona muricata L leaves ethanolic extract 180 mg plus glibenclamide during thirty days produced better glycemic control in type 2 diabetic patients.